Analisis Faktor yang Mempengaruhi Kualitas Hidup Pasien Kanker Payudara dengan Limfedema - Bella, Rosalinda; Allenidekania, Allenidekania; Nuraini, Tuti (Journal of Telenursing (JOTING), 2024)
This study aims to determine the factors that influence the quality of life of breast cancer patients with lymphedema. The research method used is a systematic review through databases and electronic websites, namely Pubmed, Proquest, EbscoHost, and Embase. The results of the study showed that the 10 research articles explained factors that influence quality of life, including operations involving the removal of a number of lymph nodes thereby increasing the possibility of lymphedema, the degree of lymphedema which affects the physical domain, mental domain, social domain and sexuality domain, as well as the accuracy of handling lymphedema. In conclusion, anticipating the impact of lymphedema will improve the quality of life of breast cancer patients. Keywords: Breast Cancer, Lymphedema, Quality Of Life